Penerapan Arsitektur Microservices pada Sistem Informasi Penjualan Online untuk Meningkatkan Skalabilitas dan Kinerja Sistem - Rosyid Fadillah Nurrokhim; Fahrul Febriansyah Siregar; Ferdy Al Firdaus; Rizki Aditiya; Faizal Muhammad Yahya; Lutfiandra Pohan; Ryan Satria Pratama (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
This study discusses the application of microservices architecture in online sales information systems as a solution to the limitations of monolithic architecture in terms of scalability and performance. Using the Software Development Life Cycle (SDLC) method of the Waterfall model, the system is built by dividing applications into small, independent services and communicating with each other through a REST API in JSON format. The implementation is carried out using Node.js, ReactJS, and Docker technologies to support more efficient management and isolation of the system. The results of the study show that the application of microservices architecture is able to improve data processing efficiency and system development flexibility. However, the complexity of managing communication between services through API Gateway is a challenge that needs to be considered in implementation. Overall, this study confirms that microservices architecture is a relevant and effective approach in the development of online sales information systems, especially to support the scalability, performance, and sustainability needs of future application development.